Developing Resilient Power Supply. Case Study: CVM Corp's Eastern Block - Erni Nur'Ainy; Akbar Adhi Utama (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to develop a strategic plan for power infrastructure to support the expansion of production capacity at CVM CORP, with a particular focus on the Eastern Block. The implementation of Eco Mechanized Mining has encountered several key obstacles, including insufficient power supply capacity, high operational electricity costs, slow response to power outages, and significant delays in the development of a new Switching Station (SS), which has been under planning since 2018. Through Current Reality Tree (CRT) analysis, the main root cause was identified as the overreliance on SS TEU as the sole power source for the entire operational zone. To address these issues, the proposed strategy includes the development of a new Switching Station near the company’s PLTU (steam power plant), determination of the optimal site using the Analytic Hierarchy Process (AHP), project scheduling via the Critical Path Method (CPM), cost-efficiency evaluation using full costing and the Levelized Cost of Electricity (LCOE), and investment feasibility analysis utilizing IRR, NPV, and Payback Period metrics. Additionally, the load distribution between SS TEU and the proposed new SS has been redesigned to enhance power efficiency and lower electricity expenses. The results show that a hybrid electricity supply model (PLN–PLTU) substantially reduces electricity costs and helps achieve production targets. The investment also demonstrates strong financial viability, with an IRR of 1398%, a Net Present Value (NPV) exceeding IDR 4.47 trillion, and a payback period of just one year. Project implementation is targeted to start by July 19, 2025, and be completed before October 21, 2026, with continuous risk mitigation throughout the execution phase. This comprehensive strategy ensures greater reliability of the power system and strengthens long-term operational resilience for CVM CORP.